Analysis of Combustion Quality on Auxiliary Boiler Performance Using Heat Loss Method - Elli Prastyo; Tegar Regi Setiawan; Farkhatus Solikha (Universitas Muhammadiyah Purwokerto, 2025)
Boiler is one type of vessel that is closed and has the main function as a means of converting energy from water into steam / steam. A good combustion process is able to produce a minimal amount of flue gas and is able to increase thermal efficiency. The value of efficiency is important because it can save operating costs and increase product productivity in auxiliary boilers. This report is based on direct observations to the company PT Trans-Pacific Petrochemical Indotama. Data collection is carried out through interviews and boiler operational logsheet data collection. The research activities will be carried out on January 2 – February 28, 2023. The purpose of this study is to determine the performance of auxiliary boilers in terms of thermal efficiency and combustion reactions that occur using the heat loss method. The variables used in this study are fuel gas flow rate, theoretical air requirements, O2 excess value, flue gas temperature, and efficiency in auxiliary boilers at PT TPPI. The results of actual data and calculations per six days in one month in January 2023 obtained an average value of fuel gas of 4544.34 m3 / hr, theoretical air of 140658.02 m3 / hr, flue gas of 54964.83 m3 / hr, and the average value of thermal efficiency in auxiliary boilers is 63.44%. The results showed that the thermal efficiency value of PT TPPI's auxiliary boiler was still suitable for use with an efficiency value standard set above 60%.